Early Childhood Fine Art Learning - Elisa Pitria Ningsih (Journal of Gemilang, 2024)
Art has been an important part of human development for a long time, one type of art is fine art. Fine art is a field of art that involves the creation of visual works, both in two-dimensional and three-dimensional form. The aim of this research is to describe the fine arts activities of early childhood. The research method used is a literature study that utilizes existing library sources. Fine arts in PAUD cannot be separated, many learning activities carried out in PAUD utilize fine arts such as painting and coloring, playing with clay or sand, collage, finger painting, drawing with sand, using recycled materials, decorating or painting. plant's pot. Activities that provide benefits for children are not only in the artistic aspect but also in other developmental aspects.